KOMUNIKASI PELAYANAN PUBLIK OMBUDSMAN RI PROVINSI RIAU DALAM PENANGANAN PENGADUAN MASYARAKAT DENGAN PENDEKATAN PROGRESIF DAN PARTISIPATIF (PROPARTIF) - Syafitri, Salsabila; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The propartive approach is a conflict management innovation in handling complaints in the Indonesian Ombudsman and has been applied to all of its representative offices, one of which is the Indonesian Ombudsman Representative of Riau Province. The use of a propartive approach in handling complaints has an impact on the decrease in the number of reports of public complaints and the convenience of the Assistant Ombudsman in completing community reports. The purpose of this study is to find out and understand how attitudes, processes and skills as a basis for a propartive approach are used in the Representative Ombudsman of Riau Province.This study uses a qualitative method. The research informants were selected through a purposive sampling technique and there were additional informants from the community selected through a random side technique whose reports were being handled or had been handled by the ombudsman. Data collection techniques carried out through interviews, observation and documentation. Data analysis techniques using Miles and Huberman include three stages, namely data reduction, data presentation and drawing conclusions. Data validity checking techniques with source triangulation.From the results of the study obtained the following results; (1) Attitude. In terms of the attitude to handle complaints, the Ombudsman is acting towards both the reporter and the reported party. The attitude towards the reporter includes openness, honesty, and curiosity, while the attitude towards the reporter is neutral with the aim of not influencing the results of the Ombudsman's suggestion for the reported party. Process. The process of handling complaints through 2 (two) ways, namely with a formal approach and informal approach. Formal approach means through standard procedural, while through informal approach using propartive in it. This propartive approach can be used directly with face-to-face meetings by understanding the propartive process circle, and can be used bye phone through whatss app communication media or direct telephone. (3) Skills. Skills in handling complaints with propartif include LSD, Reframing, Peeling the Onion whose aim is to direct the Assistant Ombudsman how to explore the hopes and interests of the public report, in addition there are also skills to persuade and educate the reported party. However, if in this case both the complainant and the reported are against, the Ombudsman uses repressive skills.